Materi Dalam Filsafat Pendidikan Islam - Abdi, Muhammad IWan (Al-Riwayah : Jurnal Kependidikan, 2018)
Islamic education philosophy is an educational philosophy based on Quran and al-Sunnah as a source of Islamic teachings. In addition, Islamic education philosophy also adopts sources from others that are not contrary to Islamic teachings. Thus, the source of guidance for Islamic education philosophy consists of two categories: the source of normative and historical sources. Normative sources are sources derived from the Quran and al-Sunnah (nash); while the historical source is a thought about the philosophy of Islamic education adopted from outside of Islamic teachings. Thus, there are three schools in the philosophy of Islamic education: the liberal, conservative, and critical groups that combine the two earlier groups (sholih li kulli zaman wa makan). This paper will discuss the subject matter of Islamic education philosophy and the sources of the three groups of flow by discussing the elements contained in the teachings of Islam, such as God, man, and nature. The purpose of this paper is to provide an understanding that the basic principles contained therein can be applied in Islamic education